TRENDS IN INNOVATIVE DEVELOPMENT OF THE STATE’S AGRICULTURE - VLASENKO, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Ensuring the competitiveness of enterprises of the agro-industrial complex (APC) and improving the quality of manufactured products is largely determined by the financial support of the industry, advanced technologies and high-performance equipment, the level of personnel training for their use, and optimization of management. In the conditions of globalization of the economy and the formation of a post-industrial society, increasing competition in the market of agricultural products, the importance of innovative activities in the industry is increasing. When designing innovative policy, both at the level of the state and a separate economic entity, it is necessary to take into account the processes of digitalization of all spheres of economic life and changes occurring in public consciousness. Agricultural enterprises have a number of additional problems caused by increased risk in this area, unstable financial situation, changes in the structure of the distribution of labor resources, underdeveloped infrastructure. The need to ensure the country’s food security and meet the population’s growing need for high-quality food products at reasonable prices prompt agricultural enterprises to implement innovative projects actively. Innovation management at the current stage involves the active use of the potential of digitization at all stages of the product life cycle. Among the main challenges facing the international and national development policy of countries in the context of global sustainable development, one of the main ones is the sustainable development of agricultural productivity to meet growing demand, increasing the efficiency of resource use worldwide to meet the growing and changing demand for food, and also stop environmental degradation. Implementation of innovative strategies by enterprises of the agro-industrial sector is the main driver of productivity growth and sustainable use of resources.